Inheritance Law: Conceptions of Inheritance According to Minangkabau Customary Law - Yetti, Yetti; Winstar, Yelia Nathassa; Indra, Faizal (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Minangkabau customary inheritance law has always been a matter of debate. This may be because Minangkabau traditional inheritance law is unique and distinctive compared to traditional inheritance law systems in other regions in Indonesia. As a result, inheritance law is also affected by Minangkabau dualization which originates from the partnership paradigm in Minangkabau marriages. This research uses normative legal research methods. In this research, it was found that according to Minang Kabau Customary Law, the process of inheritance and distribution of inheritance is often influenced by cultural values and norms that exist in Minangkabau society.